Anti-amphiphysin encephalitis: Expanding the clinical spectrum - Sun, Yueqian; Qin, Xiaoxiao; Huang, Danxia; Zhou, Ziqi; Zhang, Yudi; Wang, Qun (Frontiers in Immunology, 2023)
Objective: An analysis of the clinical features of autoimmune encephalitis accompanied by anti-amphiphysin antibodies. Methods: The data of encephalitis patients with anti-amphiphysin antibodies were retrospectively evaluated, including demographics, neurological and laboratory findings, imaging, treatment, and prognostic predictions. Results: Ten patients aged between 29 and 78 years (median age 52 years) were included. The male: female ratio was 4:6. Limbic encephalitis was found in nine patients while epileptic seizures were present in seven patients. All patients showed anti-amphiphysin antibody positivity in sera while only one showed positivity among nine CSF samples. The EEG findings were abnormal, including reductions in background activity, and the presence of diffuse slow waves, sharp waves, and spikes and waves. Five patients showed signs of increased T2 signals in the medial temporal lobe on MRI while PET showed either hyper- or hypo-metabolic changes in several brain regions, including the temporal lobe, hippocampus, basal ganglia, frontal and parietal cortices. Nine of ten patients were treated with immunotherapy, with improvements of varying degrees. There was a significant reduction in seizure frequency, and all patients were seizure-free at last follow-up. Conclusion: Autoimmune encephalitis with anti-amphiphysin antibodies has a variety of clinical manifestations. The most common symptom is limbic encephalitis. Although relief from seizures can be achieved relatively easily, many patients suffer psychiatric, cognitive, and sleep sequelae. The disease was found to be associated with a lower incidence of cancer than has been previously reported for paraneoplastic neurologic syndromes.